Optimizing Team Dynamics: An Assessment of Physician Trainees and Advanced Practice Providers Collaborative Practice*. Issue 9 (September 2016) - Foster, Cortney B.; Simone, Shari; Bagdure, Dayanand; Garber, Nan A.; Bhutta, Adnan
Abstract : Objectives: The presence of advanced practice providers has become increasingly common in many ICUs. The ideal staffing model for units that contain both advanced practice providers and physician trainees has not been described. The objectives of this study were to evaluate ICU staffing models that include physician trainees and advanced practice providers and their effects on patient outcomes, resident and fellow education, and training experience. A second aim was to assess strategies to promote collaboration between team members. Data Sources: PubMed, CINAHL, OVID MEDLINE, and Cochrane Review from 2002 to 2015. Study Selection: Experimental study designs conducted in an ICU setting. Data Extraction: Two reviewers screened articles for eligibility and independently abstracted data using the identified search terms. Data Synthesis: We found 21 articles describing ICU team structure and outcomes. Four articles were found describing the impact of advanced practice providers on resident or fellow education. Two articles were found discussing strategies to promote collaboration between advanced practice providers and critical care fellows or residents. Conclusions: Several articles were identified describing the utilization of advanced practice providers in the ICU and the impact of models of care on patient outcomes. Limited data exist describing the impact of advanced practice providers on resident and fellow education and training experience. In addition, there are minimal data describing methods to enhance collaboration between providers. Future research should focus on determining the optimal ICU team structure to improve patient outcomes, education of trainees, and job satisfaction of team members and methods to promote collaboration between advanced practice providers and physicians in training. Abstract : Supplemental Digital Content is available in the text.